Coffee Melanoidin‐Based Multipurpose Film Formation: Application to Single‐Cell Nanoencapsulation. Issue 3 (17th February 2020) - Kim, Ji Yup; Kim, Seulbi; Han, Sol; Han, Sang Yeong; Passos, Cláudia P.; Seo, Jeongyeon; Lee, Hojae; Kang, Eunhye K.; Mano, João F.; Coimbra, Manuel A.; Park, Ji Hun; Choi, Insung S.
Abstract: The melanoidin from soluble coffee is utilized as a material‐independent, multipurpose coating material. Instantaneous complexation of the coffee melanoidin (CM) with ferric ion (Fe 3+ ) leads to surface‐adhesive aggregates, inducing sequential film deposition. Various chemical groups of the CM also allow for post‐functionalizations of the CM film, including surface‐initiated, ring‐opening polymerization and bioinspired silicification. In addition, the CM‐based coating is applied to single‐cell nanoencapsulation with a strategy of biphasic interfacial reactions. The method is highly cytocompatible (viability >98%), and the CM shell is cytoprotective against lytic enzymes. The coated cells inherit the characterictics of the CM, such as post‐functionalizability and antioxidant property. Considering that surface‐coating technologies with cytocompatible natural polymers have widely been used for engineering bioentities, the CM‐based coating strategy would provide an advanced option for biomedical applications. Abstract : Coffee at its best : The coffee melanoidin (CM) is suggested as a surface‐engineering material for multipurpose, universal coating. The extremely high cytocompatibility of the CM, in addition to its post‐functionalizability, is taken advantage of for single‐cell nanoencapsulation by biphasic supramolecular self‐assembly of Fe 3+ and CM.